Parking summon system for municipal councils / Yee Hon Weng - Yee, Hon Wong (2004)
Parking Summon System for Municipal Councils (e-Summon System) is a complete system designed to ease the workload of officers in enforcing the parking laws. It aims to serve as platform for local municipal councils to improve the efficiency of collecting compound and thus, improving the parking management as a whole. e-Summon System will comprised of two main components, the PDA to issue compound notices and a main database to keep track of the issued notice. The system is devised to be employed by enforcing officers, data administration and cashiers handling the collection of fines.